Passive lower leg stiffness changes during a 10 k run - Nguyen, Anh Phong; Bosquet, Laurent; Mahaudens, Philippe; Detrembleur, Christine (Frontiers in Sports and Active Living, 2025)
The primary aim of this study was to assess lower limb stiffness in healthy runners over the course of a 10 km race at a competitive pace, with a secondary focus on investigating the tissue-specific changes in stiffness of lower limb structures during the running event. Twenty participants (3 women and 17 men) were recruited for this study. Passive stiffness measurements were assessed on the Achilles tendon, medial gastrocnemius, patellar tendon, and plantar fascia using a myotonometry device. Measurements were recorded before, during, and after the 10 k run. Our findings reveal a moderate decrease of 7% (p = 0.044, hedge's g = 0.51) of the plantar fascia's passive stiffness at the end of the trial. Contrary to the initial hypothesis, which predicted a decrease in Achilles tendon stiffness during the race, our study findings indicate that the stiffness of the Achilles tendon, patellar tendon, and medial gastrocnemius remained constant. The plantar fascia finding is novel as few studies explore foot myofascial tissue. Further investigation is warranted to elucidate the mechanisms behind the differential response of the plantar fascia compared to other tissues during prolonged running activity.